Management of Corneal Ulcers : A Systematic Review of Treatment Options - Afriadi; Miftakhul Baiti (International Medical Journal Corp. Ltd, 2026)
Introduction: Corneal ulcers represent a significant cause of ocular morbidity and potential vision loss worldwide. The management landscape is diverse, encompassing antimicrobial therapy, anti-inflammatory agents, surgical interventions, and novel adjunctive treatments. A systematic synthesis of high-quality evidence is crucial to inform optimal, evidence-based clinical strategies. Methods: A systematic review was conducted following a pre-defined protocol. Eighty studies, including randomized controlled trials (RCTs), systematic reviews, and meta-analyses, were included after screening based on strict criteria focusing on human studies of corneal ulcers reporting clinical outcomes. Data extraction covered study design, ulcer characteristics, interventions, healing, visual, and safety outcomes. Results: For bacterial keratitis, fluoroquinolone monotherapy (e.g., moxifloxacin) demonstrated equivalent efficacy to fortified antibiotic combinations but with a better ocular tolerability profile (McDonald et al., 2014; Sharma et al., 2013). Adjunctive corticosteroids showed no overall benefit in the SCUT trial but provided significant visual improvement in severe, centrally-located, non-Nocardia ulcers when initiated early (≤3 days) (Srinivasan et al., 2012; Ray et al., 2014). For fungal keratitis, natamycin was superior to voriconazole for filamentary fungi, particularly Fusarium (Sharma et al., 2015; Qiu et al., 2015). Surgical adjuncts like amniotic membrane transplantation (AMT) reduced healing time by approximately 4 days (Ting et al., 2021), while photoactivated chromophore for keratitis-corneal cross-linking (PACK-CXL) showed promise in expediting healing but with variable results based on ulcer severity and etiology (Ting et al., 2019). Discussion: The evidence supports a stratified treatment approach. Key determinants of management success include accurate etiological diagnosis, consideration of ulcer severity and location, and the timing of adjunctive interventions. Geographic variations in causative organisms and antibiotic resistance patterns necessitate local guideline adaptations. Conclusion: Effective management of corneal ulcers requires a tailored, multi-modal strategy. First-line antimicrobial choice should be guided by suspected etiology and local resistance patterns. Adjunctive corticosteroids and surgical interventions like AMT or CXL have defined, selective roles based on specific clinical and microbiological parameters. Future research should focus on high-quality RCTs in diverse populations, standardized outcome measures, and the development of personalized treatment algorithms.